2017
DOI: 10.1002/adfm.201702589
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Serpentine Interconnects on Ultrathin Elastomers for Stretchable Electronics

Abstract: Integrating deformable interconnects with inorganic functional materials establishes a path to high-performance stretchable electronics. A number of applications demand that these systems sustain large deformations under repetitive loading. In this manuscript, the influence of the elastomeric substrate on the stretchability of serpentine interconnects is investigated theoretically and experimentally. Finite element analyses (FEA) reveal a substantial increase in the elastic stretchability with reductions in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
100
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 40 publications
2
100
0
Order By: Relevance
“…Such elastomeric conductors must have metal‐like electrical conductivity that is stable under repeated mechanical deformations, such as stretching, bending, and compression . Several approaches have been attempted to achieve the desired electrical and mechanical performance, including serpentine or fractal‐based layout design, chemical reduction of a metal precursor, and incorporation of conductive fillers with a high aspect ratio (i.e., metal nanowires (metal NWs) or carbon nanotubes (CNTs)) . However, to our knowledge, the elastomeric conductors based on nanomaterials reported to date have not exceeded an electrical conductivity of ≈10 5 S cm −1 (e.g., electrical conductivity of bulk gold and bulk iron ≈ 4.1 × 10 5 and 1.0 × 10 5 S cm −1 , respectively), despite the incorporation of a high loading amount of conductive nanomaterials into the elastomers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such elastomeric conductors must have metal‐like electrical conductivity that is stable under repeated mechanical deformations, such as stretching, bending, and compression . Several approaches have been attempted to achieve the desired electrical and mechanical performance, including serpentine or fractal‐based layout design, chemical reduction of a metal precursor, and incorporation of conductive fillers with a high aspect ratio (i.e., metal nanowires (metal NWs) or carbon nanotubes (CNTs)) . However, to our knowledge, the elastomeric conductors based on nanomaterials reported to date have not exceeded an electrical conductivity of ≈10 5 S cm −1 (e.g., electrical conductivity of bulk gold and bulk iron ≈ 4.1 × 10 5 and 1.0 × 10 5 S cm −1 , respectively), despite the incorporation of a high loading amount of conductive nanomaterials into the elastomers.…”
mentioning
confidence: 99%
“…
including serpentine or fractal-based layout design, [9,10] chemical reduction of a metal precursor, [11][12][13] and incorporation of conductive fillers with a high aspect ratio (i.e., metal nanowires (metal NWs) or carbon nanotubes (CNTs)). [14][15][16][17] However, to our knowledge, the elastomeric conductors based on nanomaterials reported to date have not exceeded an electrical conductivity of ≈10 5 S cm −1 (e.g., electrical conductivity of bulk gold and bulk iron ≈ 4.1 × 10 5 and 1.0 × 10 5 S cm −1 , respectively), despite the incorporation of a high loading amount of conductive nanomaterials into the elastomers.The inadequately low conductivity of existing elastomeric conductor is due to the contact resistance between neighboring conductive components or the intrinsically low conductivity of the carbon-based materials used.
…”
mentioning
confidence: 99%
“…For example, the maximum stretchability in sinusoidal‐shaped serpentine is about 57%, regardless of other limiting factors, such as serpentine width. Analytical studies on geometrical factors and stretchability have been reported elsewhere . In addition, serpentine networks naturally result in low areal fill factor configuration of the materials or devices, i.e., the ratio between the actual area of the material and the area of the structure occupied.…”
mentioning
confidence: 99%
“…This result could be reduction of the effective stretching stiffness of the combined a high aspect ratio serpentine structure and PDMS substrate due to the decrease in elastic modulus of substrate. As a result, the entire serpentine structure and PDMS substrate can stretch in perpendicular direction with reduced strain at the peak of serpentine wave . Considering the elastic limits of typical noble metals (≈2.0%), a strategy based on decreasing the Young's modulus below 150 kPa (≈30:1 PDMS) is expected to provide high aspect ratio serpentine TC with an elastic stretching ability in excess of 100% applied strain …”
mentioning
confidence: 99%
“…As a result, the entire serpentine structure and PDMS substrate can stretch in perpendicular direction with reduced strain at the peak of serpentine wave. [38] Considering the elastic limits of typical noble metals (≈2.0%), a strategy based on decreasing the Young's modulus below 150 kPa (≈30:1 PDMS) is expected to provide high aspect ratio serpentine TC with an elastic stretching ability in excess of 100% applied strain. [10] Figure 3b illustrates the effect of the height (aspect ratio) of the Au high aspect ratio serpentine structures, 40 nm in width and with a PDMS substrate 150 kPa Young's modulus, on the 100% applied strain.…”
mentioning
confidence: 99%